Yarn periodical errors determination using three signal processing approaches - Carvalho, Vítor (2013)
This paper presents a study developed for identifying the type and location of yarn periodical errors applying three different signal processing approaches based on FFT – Fast Fourier Transform, FWHT – Fast Walsh – Hadamard Transform and FDFI – Fast Impulse Frequency Determination. Commercial equipment uses exclusively a FFT approach which is not able to clearly detect other yarn periodical types of errors, especially impulse errors. The theoretical description of each signal processing technique is presented, as well as their application to several simulated errors, namely, sinusoidal errors, rectangular errors, pulse errors and impulse errors.